FLT3 ligand in acute myeloid leukemia: a simple test with deep implications. Issue 2 (28th January 2021) - Peterlin, Pierre; Chevallier, Patrice; Knapper, Steven; Collin, Matthew
Abstract: In contrast to Fms-like tyrosine kinase 3 (FLT3), the influence of FLT3 ligand (FLT3L) on acute myeloid leukemia (AML) biology and disease prognosis has been poorly described. Here we provide an overview of the role played by FLT3L in AML. While being a cytokine implicated in the regulation of hematopoiesis, both in normal situation and after intensive chemotherapy, FLT3L has also a role in enhancing proliferation, inhibiting apoptosis and conferring resistance to FLT3 inhibitors in AML. Moreover, recent independent data show how its measurement may be helpful in the disease management. Indeed, FLT3L could provide a low cost, rapid and noninvasive assessment of chemosensitivity and blast clearance that has robust prognostic significance for patients with AML.